THE ROLE OF BUMDES KARYA ABADI IN IMPROVING THE COMMUNITY ECONOMY THROUGH THE SURUNGAN MARKET - Helen, Rachelia; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This research aims to describe and analyze the role of BUMDes in improving the community economy through the suurngan market. Method: the method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Results: The results of this study indicate that First, the provision of administrative functions runs well through strategic planning, structured organization, and responsive supervision. Second, the provision of public services has met basic needs such as public facilities and communication with traders, but has not been fully digitized. Third, Participation in Policy Making and Implementation is still at a consultative level, with dominant policy decisions in the hands of the village government and BUMDes. Fourth, Public resource management shows a social orientation through scholarship and social assistance programs, but public transparency and technology utilization are still limited. Novelty: This study provides a new perspective by combining the analysis of the role of BUMDes using Chandler and Plano indicators in the context of declining market turnover. This study emphasizes the need to strengthen digitalization, increase substantive community participation, and data-driven evaluation as strategies to make market management more effective, inclusive, and sustainable.